STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMPN 1 TINAMBUNG KABUPATEN POLEWALI MANDAR - Nurwakiah; Ahmad Hakim; M. Akil; Surani; Ratika Nengsih; Hasibuddin Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nurwakiah. The Leadership Strategies of the School Principal in Improving the Quality of Learning at SMP Negeri 1 Tinambung (supervisedby Dr. H. Ahmad Hakim, MA and Dr. H. M. Akil, MH) Learning quality at SMP Negeri 1 Tinambung in Polewali Mandar Regency still shows significant disparities, evident in variations in student learning outcomes, difficulties faced by some teachers in implementing innovative teaching methods tailored to students’ characteristics, and supervision and guidance of teachers that have not been fully optimized. The research aims to: (1) To describe the school principal’s leadership strategies in improving learning quality at SMP 1 Tinambung. (2) To analyze the supporting and inhibiting factors of the school principal’s leadership strategies. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results indicate that the principal implements strategies including systematic teacher academic supervision, fostering a school culture that is religious, disciplined, and participatory, and optimizing learning management through curriculum development, provision of facilities, and enhancement of learning evaluation quality. These strategies are supported by teacher commitment, collaboration among school members, and community support, while limited facilities, variations in teachers’ abilities, and differences in student characteristics act as inhibiting factors. In conclusion, well-planned, participatory, and consistent leadership strategies directly contribute to sustainably improving learning quality at SMP Negeri 1 Tinambung.